2022
DOI: 10.1021/acsnano.1c06410
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal Photothermal-Pharmacotherapy to Remodel Adipose Tissue for Obesity and Metabolic Disorders

Abstract: Despite the increasing prevalence of obesity, the current medications, which act indirectly on the central nervous system to suppress appetite or on the gastrointestinal tract to inhibit fat absorption, suffer from poor effectiveness and side effects. Here, we developed a transdermal mild photothermal therapy directly acting on the root of evil (subcutaneous white adipose depot) to induce its ameliorating remodeling (browning, lipolysis, and apoptosis), based on the injectable thermoresponsive hydrogel encapsu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 54 publications
1
25
0
Order By: Relevance
“…HSF1 and PGC1α then physically interact with each other and co-transactivate heat shock proteins (HSPs) including Hsp70 to maintain proteostasis and achieve cellular protection from thermal insults ( Xu et al., 2016 ). Nevertheless, Zan's study and ours both supported the notion that hyperthermia is sufficient to induce metabolic reprogramming of white fat browning in beige fat for thermogenesis and energy expenditure with a relatively wide temperature range ( Li et al., 2022 ; Zan et al., 2022 ), although for a safe and comfortable intervention, a lower and milder heat would be more preferable. The present study provides a proof-of-concept of LHT on beige fat in rodents and humans, while future investigation to define the temperature, endurance, and frequency for optimal LHT-treating efficacy and energy homeostasis, as well as novel delivery strategies for LHT on beige fat, is warranted.…”
supporting
confidence: 57%
See 1 more Smart Citation
“…HSF1 and PGC1α then physically interact with each other and co-transactivate heat shock proteins (HSPs) including Hsp70 to maintain proteostasis and achieve cellular protection from thermal insults ( Xu et al., 2016 ). Nevertheless, Zan's study and ours both supported the notion that hyperthermia is sufficient to induce metabolic reprogramming of white fat browning in beige fat for thermogenesis and energy expenditure with a relatively wide temperature range ( Li et al., 2022 ; Zan et al., 2022 ), although for a safe and comfortable intervention, a lower and milder heat would be more preferable. The present study provides a proof-of-concept of LHT on beige fat in rodents and humans, while future investigation to define the temperature, endurance, and frequency for optimal LHT-treating efficacy and energy homeostasis, as well as novel delivery strategies for LHT on beige fat, is warranted.…”
supporting
confidence: 57%
“…Interestingly, using specific small interfering RNAs, we found that the mild hyperthermia used in our study (41°C) requires HSF1, but not TRPV1, which is inconsistent with a reported threshold of 43°C for TRPV1 activation. Notably, another recent report used 45°C transdermal photothermal–pharmacotherapy in adipose tissue to ameliorate obesity and metabolic disorders and found that TPRV1 may mediate the effects of this relatively high temperature by increasing the intracellular calcium concentration and engaging in downstream thermogenic gene programs ( Zan et al., 2022 ), though it did not exclude the possible involvement of HSF1 in this process. Indeed, we have previously shown that HSF1 responds to heat of 42°C–45°C and induces PGC1α expression.…”
mentioning
confidence: 99%
“…Besides for this, stimuli-hydrogels are also recently explored for highly effectively treating obesity combined with nanomaterials. Recently, Chen's group incorporated copper sulfide nanodots (CuS-ND) into injectable thermo-responsive hydrogel to induce the ameliorating remodeling based on directly acting on the root of evil according to transdermal mild photothermal therapy [ 188 ]. Simultaneously, mirabegron was further co-delivered with such hydrogels, inducing a strong therapeutic synergy.…”
Section: Non-cancer Therapy Of Nanomaterials Incorporated Polymeric P...mentioning
confidence: 99%
“…27 To date, hydrogels have been applied in various fields. [28][29][30][31][32][33][34] Among them, the extracellular matrix (ECM)-like property and excellent biocompatibility of hydrogels enable their outstanding application potential in biomedical fields. [35][36][37] Hydrogels as wound dressings have been successfully used to promote tissue regeneration including skin wound repair.…”
Section: Introductionmentioning
confidence: 99%